Strategi Pemasaran Badan Usaha Milik Pesantren - Imroni Hasan (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2021)
The existence of pesantren has an important meaning in solving community economic problems related to unemployment and poverty. It is important for pesantren to organize entrepreneurship education as a medium in introducing the business world as well as motivating students to become entrepreneurs. Entrepreneurship education is expected to build the interest of students to become successful entrepreneurs after completing their education at pondok pesantren to open new job opportunities. This study focuses on marketing strategies, supporting and inhibiting factors in business entities owned by pesantren, especially in pesantren Manarul Qur'an. The research design used in this study is a type of field research with a qualitative descriptive method. Data collection techniques through documentation, observation and interviews. Pesantren-Owned Enterprises are a Pesantren Business Center to develop businesses to be more independent in obtaining finances, in its development to achieve the goals to be achieved, it cannot be separated from a marketing strategy which consists of several elements including a marketing strategy by analyzing community needs, the art of identifying and taking advantage of opportunities. that appear in the market, and product pricing, product sales promotion. While the supporting factors are professional managers, adequate facilities and infrastructure and high public trust, and for inhibiting the lack of community response and the location of pensantren in remote areas. It is important to do further research related to online-based marketing strategies.